EFEKTIVITAS BIMBINGAN KLASIKAL DENGAN METODE DISKUSI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Hikmah Saptiani Marliana; Siti Fatimah; Reza Pahlevi (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
The research was designed to increase students' learning motivation, the method used was quantitative method with a total researchsample of 20 students through a questionnaire learning motivation questionnaire. The results showed that this quantitative dataprocessing analysis used a learning motivation scale with a reliability of 0.915. Based on the results of the Paired Sample T-test, theSig. (2-tailed) value is 0.000 <0.05, this shows the Sig. (2-tailed) value is smaller than 0.05. And the results of the n-gain test results from the mean value obtained 56% adjusted to the category obtained 56% is quiteeffective. This is also proven by the normality results which show a value of 0.128 because the significance value is more than 0.05, this shows that the data is normally distributed, so the effectiveness of classical guidance with the discussion method can increase student learning motivation.